(untitled) (Journal of Educational Sciences, 2024)
The choice of dissertation topic is a key aspect of doctoral studies, determining both the research contribution to the field of study and the trajectory of the researcher’s academic and professional career. This pilot study sought to identify relationships between the choice of dissertation topic and demographic characteristics (gender, age), status (doctoral student, PhD, graduate without defense), research direction and publication activity. It also sought to establish differences in these variables. The study involved 77 respondents. The methodology included correlation analysis, Mann-Whitney U test and Kruskal-Wallis test. The results showed positive correlations between age and status, age and sufficiency of time to choose a topic, and age and satisfaction with the chosen topic. Status positively correlated with publications in top-rated journals. The results of the study demonstrated significant differences in the aspect of scientific direction for the variable independence of choosing a dissertation topic. The authors haven’t found any differences in the studied variables in terms of age, gender, status and publication activity. The useful ideas for future research on the problem of choosing a dissertation topic by doctoral students are proposed. The practical significance of the study is that understanding the relationships and differences between topic choice, demographic data, status and publication activity can help develop effective strategies for supporting doctoral students. Key words: doctoral studies, PhD, research topic, dissertation, choice of topic.